Denied odors of the aging body in the processes of significance of abuse in contemporary Chile - Guajardo Soto, Gabriel (Estado, Gobierno y Gestión Pública, 2018)
Body odor in its relation with mistreatment towards elderly has had fewattention from research in the field of violence studies. This article adresses thesubject starting from the results of cualitative research based on 4 discussiongroups and 4 focus groups executed with the participation of self-reliantelderly between the years 2012 and 2014, Región Metropolitana, Chile. Theresults are the following: in middle-high and middle socioeconomic status,taboos and stigma concerning excrement and urine odors are spontanouslymentioned by participants. In the mid-low and low socioeconomic status,odors concerning aged bodies do not constitute a mark. Women, old mothersand grandmothers are most likely to be the subjects of rejected odors;older men do not appear in social discourse. Finally, the article discussesthe necesity to consider different dimensions and uses of the body in thedelimitation of the public problem of violence towards old aged people.